Preoperative plasma aldosterone and the risk of atrial fibrillation after coronary artery bypass surgery: a prospective cohort study. Issue 12 (December 2016) - Alexandre, Joachim; Saloux, Eric; Chequel, Mathieu; Allouche, Stéphane; Ollitrault, Pierre; Plane, Anne-Flore; Legallois, Damien; Fischer, Marc-Olivier; Saplacan, Vladimir; Buklas, Dimitrios; Labombarda, Fabien; Blanchart, Katrien; et al.
Abstract : Objective: Postoperative atrial fibrillation (POAF) is associated with poor outcomes after coronary artery bypass graft (CABG) surgery. We aimed to assess the additional value of preoperative plasma aldosterone levels, a biomarker promoting proarrhythmic and profibrotic pathways, for predicting POAF after CABG. Methods: We conducted a prospective cohort study involving consecutive patients with left ventricular ejection fraction (LVEF) more than 50% requiring elective CABG in our university hospital. Plasma aldosterone levels, two-dimensional echocardiography including left atrial strain analysis and galectin-3 (Gal-3) examination were assessed before cardiac surgery. The primary endpoint was the occurrence of POAF within 30 days after surgery. Results: POAF occurred in 34 (24.8%) out of the 137 included patients. Compared with controls, patients experiencing POAF were significantly older (73 years old ± 8 vs 65 ± 11, P < 0.001) and had higher preoperative plasma aldosterone levels [183 pmol/l (interquartile range 138–300) vs 143 pmol/l (interquartile range 96.5–216.5), P < 0.01]. Age [odds ratio (OR), 1.088; 95% confidence interval (CI) (1.038–1.140); P = 0.0004] and plasma aldosterone levels [OR, 1.007; 95% CI (1.003–1.012); P = 0.0013] were independently associated with POAF in multivariate analysis and could therefore be combined to predict the occurrence of POAF ['Aldoscore', OR, 2.7; 95% CI (1.7–4.3); P < 0.0001]. Reverse transcriptase PCR analysis performed on right atrial appendage and plasma examination revealed that Gal-3 was activated in POAF patients. Conclusion: We developed the preoperative 'Aldoscore' for POAF risk stratification among patients with preserved LVEF requiring elective CABG. This new tool may be helpful to identify good responders to interventions targeting the proarrhythmic and profibrotic pathways of aldosterone. Abstract : Supplemental Digital Content is available in the text